Society's Diversity in Influencing Education (Kudus Tower Case Study in Influencing Islamic Education) - Muhammad Arief Nugroho; Ashif Az Zafi (Tarbiyatuna: Jurnal Pendidikan Islam, 2021)
The purpose of this article is to find out how Islamic education in the area around the Kudus Tower is influenced religious community, as well as to find out the influence in Islamic education. The process of compiling this study used a qualitative approach. The data collection was done by conducting a literature study. It is known that the influence of a religious community for Islamic education in the area around the Kudus tower includes making students more familiar with Islam, as well as the special attitude of Islamic education institutions in educating their students. The results obtained from this study are Islamic educational institutions around the Kudus tower are growing rapidly and these educational institutions form students who excel in academics and have noble character. The main factor in the formation of the noble character of students is caused by the kiai who become teachers in educational institutions, a religious community environment, upholding the teachings of Islam and also side by side with the tomb of Sunan Kudus which is its own value.